Novel In Silico Strategies to Model the In Vivo Nerve Scarring Around Implanted Parylene C Devices - Pier Nicola Sergi; Jaume del Valle; Thomas Stieglitz; Xavier Navarro; Silvestro Micera (Applied Sciences)
The implantation of materials into in vivo peripheral nerves triggers the production of scar tissue. A scar capsule progressively incorporates foreign bodies, which become insulated from the surrounding environment. This phenomenon is particularly detrimental in the case of electrical active sites enveloped within scar sheets, since the loss of contact with axons highly decreases the effectiveness of neural interfaces. As a consequence, the in silico modelling of scar capsule evolution may lead to improvements in the design of intraneural structures and enhancing their reliability over time. In this work, a novel theoretical framework is proposed to model the evolution of capsule thickness over time together with an improved optimisation procedure able to avoid apparently suitable choices resulting from standard procedures. This framework provides a fast, simple, and accurate modelling of experimental data (<semantics>R2=0.97</semantics>), definitely improving on previous approaches.